Synthesis of poly(4, 4′‐biphenylene sulfonyl succinamide)‐polysulfone blend membranes for removal of toxic metal ions from water. Issue 48 (13th July 2019) - Subrahmanya, T. M.; Naik, Nagaraj S.; Padaki, Mahesh; Geetha Balakrishna, R.; Jyothi, M. S.; Yadav, Sudesh; Hung, Wei‐Song
ABSTRACT: A novel polymer poly(4, 4′‐biphenylene sulfonyl succinamide) (PBSS) was synthesized via polycondensation reaction. Succinyl chloride and 4‐aminophenyl sulfone were used as reactive monomers and anhydrous AlCl3 was used as a catalyst. Both polysulfone (PSf) and PBSS were dissolved in N ‐methyl‐2‐pyrrolidone (NMP) at different compositions to obtain a homogeneous solution to fabricate PSf‐PBSS blend membranes. The structure of PBSS was characterized by ATR‐IR and 1 H‐NMR spectroscopy. Thermal properties of PBSS were analyzed by TGA‐DTA. Mechanical properties and morphology of blend membranes were analyzed by universal testing machines and field emission scanning electron microscope, respectively. The hydrophilicity of blend membranes with respect to the concentration of PBSS was studied by contact angle and water uptake studies. Upon blending, the hydrophilicity of PSf‐PBSS membranes drastically increased due to the presence of large number of amide and sulfonyl groups in the matrix. The blend membranes exhibited significant increase in water flux from 100 L m −2 h to 650 L m −2 h −1, and rejection of 100% for Pb(II) and 80% for both Cd(II) and As(III) toxic heavy metal ions. The hydrophilic nature of CONH and inter and intramolecular hydrogen bonding among PBSS polymer chains dispersed within rigid PSf matrix imparts softness, amide and sulfonyl groups enhance interconnected porosity and hydrophilicity of blend membranes. Hence, PBSS may serve as a low‐cost novel polymeric additive for water purification and separation membrane applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48254. Abstract :